PERBANDINGAN KECERDASAN EMOSI DAN PERCAYA DIRI ANTARA SISWA YANG MENGIKUTI EKSTRAKURIKULER BOLAVOLI DAN PENCAK SILAT DI SMA NEGERI 1 BLUTO - IRWANSYAH, LUTFI (Jurnal Pendidikan Olahraga dan Kesehatan, 2014)
Abstract Extracurricular activities are additional activities conducted by school activity such as sports and non-sports. Extracurricular, sports, in particular, can be a platform to build the character and cultivate individual development. Emotional intelligence and self-confidence be one of important thing which can build through sport activity. Emotional intelligent and self confidence management in every different type of sport, especially in team and individual. Volleyball is team type of sport which indeed has a different application compare with pencak silat as individual sport. This study aimed to compare emotional intelligence and self-confidence of students who comply in Volleyball and pencak silat extracurricular in SMAN 1 Bluto. This research is a quantitative research. The design used was a non-comparative experiments. In this study, the population and study object are students who comply in Volleyball and Pencak silat extracurricular. Since the number of population was under 100 (44 students), therefore, this study include the type of study population. Instrument used was questionnaire and statistical analysis of data using t-test. Based on the research results and calculate the data using SPSS 20.0 indicate value of 2.130 and 0.152 sig in emotional intelligence. This suggest that sig (0.033) < alpha 0.05, which means that Ho  is rejected and H1 is accepted. While the results indicate confidence value of 1.599 and 0.213 sig. this suggest that the mean sig (0.213) < alpha of 0.05, which means that H0 is rejected and H1 is accepted. Thus, from this study can be concluded that there is no significant difference in emotional intelligence and self-confidence between students who comply in volleyball extracurricular and pencak silat in SMAN 1 Bluto. Keywords :Penjasorkes, Nutrition status, Physical fitness.